Temperament structures and the effectiveness of individual play in football - Bojkowski, L.; Tomczak, M. (Frontiers in Psychology, 2024)
Background: Regulatory Theory of Temperament distinguishes two traits involving the time course of responses and four relating to how energy is distributed and stored. This theory enables the presentation of entire structures of temperament traits and it is relevant for assessing an individual`s ability to process stimulation and influence their performance during competitions. In our cross-sectional study, these structures are examined in relation to the offensive, defensive, and comprehensive effectiveness of an individual player`s actions.